The European iSchools. - Seadle, Michael (Bulletin of the Association for Information Science & Technology)
EDITOR'S SUMMARY Started in the late 1990s by deans of three library schools in the United States, the iSchool movement has grown to include 16 European institutions. The expansion required revision of the original North American model, assumptions about academic positions and funding. Among the European schools, some differences exist in curricular focus, though funding needs may reinforce subject area overlap. As an example, the Berlin School of Library and Information Science offers multiple programs at the bachelor's, master's and doctoral levels, with varying curricula focusing on practical librarianship, computer emphasis or extended research. The curricula at other European iSchools, their research pursuits and employment opportunities for bachelor's and master's program graduates vary widely. Most attaining a doctorate degree go into management since academic positions are limited. European iSchools collaborate through planning, exchange programs and a shared doctoral colloquium, and funding sources reward cooperative institutional efforts and geographic diversity.